Wild animal welfare and protection in international conventions - Ayşe Menteş Gürler (Eurasian Journal of Veterinary Sciences)
Due to industrialisation and population growth, the over-useage of the natural resources causes some damages on the ecological systems. Recently, the en devours for solving these issues are focused on the protection and sustainable use of the biodiversity and bequesting to the new generations. These occupations contunue at national and international level at the stage of scientific researches and legal amendments. In Turkey, the occupations on the conservation of the wild life is managed with national legislations, being part of the international conventions and also the advices and support of the international organisations. Taking consideration of transborder movements of wild animals, the measurements should be determined at international levef. The stucfy was undertaken to research wild animals welfare and protection status in the international conventions which are Turkey to party related with nature protection.